The genesis of Genesis the mytho-empiricism of creation - Shoham, S. Giora, 1929- (Newcastle upon Tyne : Cambridge Scholars, 2011)
"The Genesis of Genesis is about the mytho-empiricism of creation-- cosmogony. In its attempt to compare the mythologies of the ancient Eastern Mediterranean cultures--Egyptian, Greek, Judaic and Mesopotamian--the Judaic cosmogony of genesis, which is unique in its reliance on the word as creative agent, is contrasted with the Egyptian, Greek and Mesopotamian mythologies, which are more deterministic"--Publisher.
Includes bibliographical references (p. [301]-311).
Description based on print version record.
Keywords: Creation -- Comparative studies; Beginning; Cosmology -- Comparative studies; Dualism; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; RELIGION / Theology; Electronic books